Learning Strategies in the Digital Era: Innovative Approaches for Elementary Schools - Hanama, Akhmad; Hidayati, Dian (Indonesian Journal of Educational Science and Technology, 2024)
The development of technology and information has influenced various aspects of human life, including education. With these changes, the education sector requires adjustments in learning strategies to align with the advancements in digital information technology. This study aims to identify suitable learning strategies for elementary schools in the digital era. It employs a qualitative research approach using a literature review method. Data were collected through an analysis of various sources, such as journals and books, and analyzed using Miles and Huberman's data analysis technique, which consists of three stages: data condensation, data presentation, and conclusion drawing. Several learning strategies can be implemented by elementary school teachers in the digital era, including the development of learning models, evaluation techniques, and learning media that leverage technology. The use of technology-based models, evaluation tools, and media is expected to facilitate students in achieving their learning objectives.